Influence of COVID-19 for delaying the diagnosis and treatment of pulmonary tuberculosis–Tianjin, China - Zhang, Guoqin; Yu, Yanming; Zhang, Wenqian; Shang, Jian; Chen, Shengyu; Pang, Xuewen; Oeltmann, John E.; Moonan, Patrick K.; Chen, Mingting; Zhang, Fan (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has disrupted tuberculosis (TB) diagnosis, treatment and care. Delays in seeking TB care may result in increased community transmission and unfavorable treatment outcomes. We sought to understand the influence of COVID-19 pandemic on the proportion of TB patients who delayed seeking TB diagnosis and care and explore the reasons for their postponement. Methods We surveyed a representative sample of outpatients treated for pulmonary TB during June–November, 2020 using an anonymous standardized questionnaire. Multivariable logistic regression was used to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CIs) of factors associated with the postponement of TB care. We used routinely collected surveillance data to assess trends of TB report before and after the emergence of COVID-19 (2017–2019 vs 2020–2022) in Tianjin, China. Results Among 358 participants who were diagnosed pulmonary TB during the COVID-19 response, 61 (17%) postponed seeking TB diagnosis due to COVID-19, with 39 (64%) cited fear as the primary reason. Female sex (aOR:2.0; 95% CI: 1.1–3.7), previous antituberculosis treatment (aOR:3.2; 95%CI: 1.4–7.6) and TB diagnosis during the first-level response (aOR=3.2, 1.7-6.2) were associated with the postponement. Among all 518 participants receiving antituberculosis treatment, 57 (11%) had postponed their regular healthcare visit due to COVID-19; 175 (34%) received no treatment supervision and 32 (6%) experienced treatment interruption. Compared to 2017–2019, reported pulmonary TB declined by 36.8% during the first-level response to COVID-19, 23.5% during the second-level response, 14% during the third-level response in 2020, and 4.3% in 2021. Conclusions The COVID-19 response reduced the number of people who sought and received TB diagnosis, treatment, and care in Tianjin, China; integrative programs to ensure access and continuity of TB services should be considered; dual testing for SARS-CoV-2 and M. tuberculosis may facilitate case-finding.